Is the diagnostic threshold for bulimia nervosa clinically meaningful?. (January 2018) - Chapa, Danielle A.N.; Bohrer, Brittany K.; Forbush, Kelsie T.
Abstract: The DSM-5 differentiates full- and sub-threshold bulimia nervosa (BN) according to average weekly frequencies of binge eating and inappropriate compensatory behaviors. This study was the first to evaluate the modified frequency criterion for BN published in the DSM-5 . The purpose of this study was to test whether community-recruited adults ( N = 125; 83.2% women) with current full-threshold ( n = 77) or sub-threshold BN ( n = 48) differed in comorbid psychopathology and eating disorder (ED) illness duration, symptom severity, and clinical impairment. Participants completed the Clinical Impairment Assessment and participated in semi-structured clinical interviews of ED- and non-ED psychopathology. Differences between the sub- and full-threshold BN groups were assessed using MANOVA and Chi-square analyses. ED illness duration, age-of-onset, body mass index (BMI), alcohol and drug misuse, and the presence of current and lifetime mood or anxiety disorders did not differ between participants with sub- and full-threshold BN. Participants with full-threshold BN had higher levels of clinical impairment and weight concern than those with sub-threshold BN. However, minimal clinically important difference analyses suggested that statistically significant differences between participants with sub- and full-threshold BN on clinical impairment and weight concern were not clinically significant. In conclusion, sub-threshold BN did not differ from full-threshold BN in clinically meaningful ways. Future studies are needed to identify an improved frequency criterion for BN that better distinguishes individuals in ways that will more validly inform prognosis and effective treatment planning for BN. Highlights: First study to evaluate DSM-5 frequency criterion for bulimia nervosa (BN). Sub- and full-threshold BN have similar levels of eating-disorder symptoms. Sub- and full-threshold BN have similar levels of non-eating-disorder symptoms. There were no clinically significant differences between sub- and full-threshold BN.